Analysis of Road Performance to Overcome Congestion at Unsignalized Intersections (Case Study: Tanjung Buntung - Batam) - Elisa Eriany Pardosi; Andri Irfan Rifa'i (LEADER: Civil Engineering and Architecture Journal, 2023)
Traffic jams and congestion at unsignalized intersections are common problems in many cities. This study aims to analyze road performance in overcoming congestion at unsignalized intersections using case studies in the Tanjung Buntung area, Batam. The research method used includes collecting traffic data such as geometric data, primary and secondary data, and data analysis using the 1997 Indonesian Highway Capacity Manual Method (MKJI). The analysis results show that this intersection experiences congestion during busy hours with high density. Alternatives that can overcome congestion at unsignalized intersections include widening the road and providing traffic signs on the side to give directions to motorists to avoid parking carelessly on the side of the intersection.